Analysis of Feminism in English-Learning YouTube Channels - Salwa Fitria Khairunnisa; Ferisa Zafira (Universitas Muhammadiyah Lampung, 2023)
This study aims to analyse the representation of feminism in three English learning channels on YouTube, namely English with Lucy, BBC Learning English, and Language & Gender (Sociolinguistics Lecture). The Feminist Critical Discourse Analysis (FCDA) approach is utilised to examine three main aspects: visual, linguistic, and narrative. The results indicate that English with Lucy exhibits a strong representation of feminism through the agency of female instructors, the use of gender-neutral language, and professional visuals that portray women as knowledge creators. BBC Learning English demonstrates a relatively balanced representation, although subtle gender biases persist in the division of instructional roles. Meanwhile, Language & Gender explicitly presents feminism through a critical discussion of the construction of gender in language. The findings confirm that YouTube functions not only as a learning medium but also as an ideological space that influences learners' understanding of gender. The implications suggest that educators, learners, and content creators should foster critical literacy in order to identify gender bias and utilise digital content that promotes equality.